Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure, let's evaluate each expression step-by-step:
### Part a:
Evaluate the expression [tex]\(-7x^3 + 3x^2 + 11x - 9\)[/tex] for [tex]\(x = -2\)[/tex].
1. Substitute [tex]\(x = -2\)[/tex] into the expression:
[tex]\[-7(-2)^3 + 3(-2)^2 + 11(-2) - 9\][/tex]
2. Next, calculate each term:
[tex]\((-2)^3 = -8\)[/tex]
[tex]\[-7 \cdot (-8) = 56\][/tex]
[tex]\((-2)^2 = 4\)[/tex]
[tex]\[3 \cdot 4 = 12\][/tex]
[tex]\[11 \cdot (-2) = -22\][/tex]
3. Combine these results:
[tex]\[56 + 12 - 22 - 9\][/tex]
4. Simplify:
[tex]\[56 + 12 = 68\][/tex]
[tex]\[68 - 22 = 46\][/tex]
[tex]\[46 - 9 = 37\][/tex]
So, the result for part a is [tex]\(\boxed{37}\)[/tex].
### Part t:
Evaluate the expression [tex]\(4y^2 - 3y + 8\)[/tex] for [tex]\(y = -3\)[/tex].
1. Substitute [tex]\(y = -3\)[/tex] into the expression:
[tex]\[4(-3)^2 - 3(-3) + 8\][/tex]
2. Next, calculate each term:
[tex]\((-3)^2 = 9\)[/tex]
[tex]\[4 \cdot 9 = 36\][/tex]
[tex]\[-3 \cdot (-3) = 9\][/tex]
3. Combine these results:
[tex]\[36 + 9 + 8\][/tex]
4. Simplify:
[tex]\[36 + 9 = 45\][/tex]
[tex]\[45 + 8 = 53\][/tex]
So, the result for part t is [tex]\(\boxed{53}\)[/tex].
### Part c:
Evaluate the expression [tex]\(14x^2y + 3xy^2 + 2xy - 5\)[/tex] for [tex]\(x = 1\)[/tex] and [tex]\(y = 2\)[/tex].
1. Substitute [tex]\(x = 1\)[/tex] and [tex]\(y = 2\)[/tex] into the expression:
[tex]\[14(1)^2(2) + 3(1)(2)^2 + 2(1)(2) - 5\][/tex]
2. Next, calculate each term:
[tex]\((1)^2 = 1\)[/tex]
[tex]\[14 \cdot 1 \cdot 2 = 28\][/tex]
[tex]\[(2)^2 = 4\][/tex]
[tex]\[3 \cdot 1 \cdot 4 = 12\][/tex]
[tex]\[2 \cdot 1 \cdot 2 = 4\][/tex]
3. Combine these results:
[tex]\[28 + 12 + 4 - 5\][/tex]
4. Simplify:
[tex]\[28 + 12 = 40\][/tex]
[tex]\[40 + 4 = 44\][/tex]
[tex]\[44 - 5 = 39\][/tex]
So, the result for part c is [tex]\(\boxed{39}\)[/tex].
In summary, the results are:
- Part a: [tex]\(\boxed{37}\)[/tex]
- Part t: [tex]\(\boxed{53}\)[/tex]
- Part c: [tex]\(\boxed{39}\)[/tex]
### Part a:
Evaluate the expression [tex]\(-7x^3 + 3x^2 + 11x - 9\)[/tex] for [tex]\(x = -2\)[/tex].
1. Substitute [tex]\(x = -2\)[/tex] into the expression:
[tex]\[-7(-2)^3 + 3(-2)^2 + 11(-2) - 9\][/tex]
2. Next, calculate each term:
[tex]\((-2)^3 = -8\)[/tex]
[tex]\[-7 \cdot (-8) = 56\][/tex]
[tex]\((-2)^2 = 4\)[/tex]
[tex]\[3 \cdot 4 = 12\][/tex]
[tex]\[11 \cdot (-2) = -22\][/tex]
3. Combine these results:
[tex]\[56 + 12 - 22 - 9\][/tex]
4. Simplify:
[tex]\[56 + 12 = 68\][/tex]
[tex]\[68 - 22 = 46\][/tex]
[tex]\[46 - 9 = 37\][/tex]
So, the result for part a is [tex]\(\boxed{37}\)[/tex].
### Part t:
Evaluate the expression [tex]\(4y^2 - 3y + 8\)[/tex] for [tex]\(y = -3\)[/tex].
1. Substitute [tex]\(y = -3\)[/tex] into the expression:
[tex]\[4(-3)^2 - 3(-3) + 8\][/tex]
2. Next, calculate each term:
[tex]\((-3)^2 = 9\)[/tex]
[tex]\[4 \cdot 9 = 36\][/tex]
[tex]\[-3 \cdot (-3) = 9\][/tex]
3. Combine these results:
[tex]\[36 + 9 + 8\][/tex]
4. Simplify:
[tex]\[36 + 9 = 45\][/tex]
[tex]\[45 + 8 = 53\][/tex]
So, the result for part t is [tex]\(\boxed{53}\)[/tex].
### Part c:
Evaluate the expression [tex]\(14x^2y + 3xy^2 + 2xy - 5\)[/tex] for [tex]\(x = 1\)[/tex] and [tex]\(y = 2\)[/tex].
1. Substitute [tex]\(x = 1\)[/tex] and [tex]\(y = 2\)[/tex] into the expression:
[tex]\[14(1)^2(2) + 3(1)(2)^2 + 2(1)(2) - 5\][/tex]
2. Next, calculate each term:
[tex]\((1)^2 = 1\)[/tex]
[tex]\[14 \cdot 1 \cdot 2 = 28\][/tex]
[tex]\[(2)^2 = 4\][/tex]
[tex]\[3 \cdot 1 \cdot 4 = 12\][/tex]
[tex]\[2 \cdot 1 \cdot 2 = 4\][/tex]
3. Combine these results:
[tex]\[28 + 12 + 4 - 5\][/tex]
4. Simplify:
[tex]\[28 + 12 = 40\][/tex]
[tex]\[40 + 4 = 44\][/tex]
[tex]\[44 - 5 = 39\][/tex]
So, the result for part c is [tex]\(\boxed{39}\)[/tex].
In summary, the results are:
- Part a: [tex]\(\boxed{37}\)[/tex]
- Part t: [tex]\(\boxed{53}\)[/tex]
- Part c: [tex]\(\boxed{39}\)[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.